Immune thrombocytopenia with clinical significance in systemic lupus erythematosus: a retrospective cohort study of 90 patients. (16th December 2021) - Roussotte, Mickaël; Gerfaud-Valentin, Mathieu; Hot, Arnaud; Audia, Sylvain; Bonnotte, Bernard; Thibault, Thomas; Lobbes, Hervé; Le Guenno, Guillaume; Goulabchand, Radjiv; Cathebras, Pascal; Varron, Loig; Dufour, Jean François; et al.
Abstract: Objectives: To describe the characteristics, treatment and outcome of patients with immune thrombocytopenia with clinical significance (ITPCS) associated with SLE. Methods: This retrospective multicentre study included SLE patients who experienced ≥1 ITPCS (defined as ITP with attributable bleeding disorders and/or a platelet count <30×10 9 /l). Other causes of secondary thrombocytopenia were excluded. Major bleeding event (MBG) was defined as Khellaf score >8 and/or WHO score >2. Results: A total of 90 patients were included, the median (range) follow-up duration was 80 (6–446) months. ITP was diagnosed before SLE in 25 patients. They presented a high rate of autoimmune haemolytic anaemia (15%), antiphospholipid antibody (62%) and antiphospholipid syndrome (19%). The 25 (28%) patients who experienced MBG had significantly more bleedings at ITP diagnosis and higher bleeding scores, and serositis and thrombosis during follow-up. They required significantly more treatment lines, transfusions and hospitalizations. The 11 (12%) patients who experienced no bleeding event presented a significantly more restricted SLE phenotype (cutaneous and/or articular). Patients received a mean (range) of 4.2 (1–11) treatment lines. Corticosteroids and HCQ allowed ITPCS overall response in one-third of patients. The median relapse-free survival of rituximab ( n = 34), AZA ( n = 19), MMF ( n = 8), thrombopoietin-receptor agonists ( n = 16) and splenectomy ( n = 19) were 53, 31.5, 61, 24.5 and 78 months, respectively. Four patients experienced thrombotic events after splenectomy and one occurred under thrombopoietin-receptor agonist treatment. Conclusion: SLE-ITCS patients displayed a high rate of haematological abnormalities and MBG patients exhibited higher morbidity. Management of thrombocytopenia was highly heterogeneous and many options seem viable.